Tech Job Hunt Handbook Career Management for Technical Professionals - Grossman, Kevin W.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2012)
Tech Job Hunt Handbook is a career management book$1 (Bjust for technology professionals$1 (Bthat reflects today$1 (Bs new economic realities. The world of work is constantly changing, and staying professionally relevant while competing for more specialized tech jobs in areas like cloud computing, mobile and social applications, and big data in a highly competitive global economy is critical. The world is churning out hungry programmers and developers in record numbers, making the global labor market highly competitive. It is now essential to plan a campaign to get a better job as well as your overall career. Retooling your skills and re-branding yourself is mandatory whether you$1 (Bre seeking a new job or intent on retaining current employment. Readers of the Tech Job Hunt Handbook will find tools, practical guidance, and recommendations on how to find the best new tech jobs, how to get noticed, how to ace interviews and get hired, and how to keep those new jobs$1 (Buntil it$1 (Bs time for a better one. As you will learn, learning how to assess and then invest in career management skills leads to long-term competitive advantage and a happier working life. Tech Job Hunt Handbook$1 (Bfor recent graduates, risk-taking innovators, and tech veterans alike$1 (Bshows how to build a comprehensive online professional profile, identify the companies you$1 (Bre interested in and who you know at those companies, approach interviews with confidence, uncover opportunities in your current company, and understand the new emerging technology markets that could lead to a career rebirth. This book will help you: Find a new or better tech job. Stay relevant and employable despite constant new developments. Manage your tech career for long-term success.s
Keywords: Economics; Economics/Management Science; Business/Management Science, general